Transfixed by prehistory : an inquiry into modern art and time - Stavrinaki, Maria (Zone Books, 2022)
"Prehistory is an invention of the later nineteenth century. It was in this moment of technological progress and the acceleration of production and circulation, that three major Western narratives about time took shape. One after another, these new fields of inquiry delved into the obscure immensity of the past: first, to reckon the age of the Earth; second, to find a point of emergence of human beings; and third, to ponder the age of art. Maria Stavrinaki's Transfixed by Prehistory considers the inseparability of these accounts of temporality from the disruptive forces of modernity. She asks what a history of modernity and its art would look like if it was considered through these three, at once consecutive and interwoven, inventions of the longue durée? This book attempts to articulate such a history, which turns out to be more complex than that of an inevitable march of progress leading up to the "Anthropocene." Rather, it's a history of stupor, defamiliarization, regressive acceleration and incessant invention, since the "new" was also found in the deep sediments of the Earth. Composed as much of speed as of slowness, as much of change as of deep time, as much of confidence as of skepticism and doubt, modernity is a complex phenomenon that needs to be thought again. This book focuses on this intrinsic tension through major artistic practices (Cézanne, Matisse, De Chirico, Ernst, Picasso, Dubuffet, Smithson, Morris, and contemporary artists such as Pierre Huyghe and Thomas Hirschhorn), philosophical discourses (Bataille, Blumenberg, and Jünger) and the human sciences. This groundbreaking book will attract readers interested in the intersections of art history, anthropology, psychoanalysis, mythology, geology, and archaeology"--